Analysis of ethnic differences of Iranian sports fans in the variables of Islamic cohesion, national identity, and perception of sports success - Hossein Monazzami, Amir (2021)
Iran is a country with different ethnicities and religions and some negative experiences of conflicts throughout history. It is believed that; Sports success is a factor in the greater convergence of a country's citizens. This article analyzes the ethnic differences of Iranian sports fans in Islamic cohesion, national identity, and perception of sports success. The research was a descriptive survey. The statistical population was all Iranians interested in national sports, 968 of whom participated in the study voluntarily. The research instruments were the researcher-made questionnaire of Perception of Sports Success, the National Identity Questionnaire of Hear and James (2007), and the Islamic Cohesion Questionnaire of Baghbanian and Morowat (2011). The content and face validity of the questionnaires were confirmed by the professors and their reliability was calculated with Cronbach's alpha coefficient of 0.78, 0.88, and 0.83, respectively. The test of hypotheses showed that; the variables of Islamic cohesion and national identity have a statistically significant difference between Shiite and Sunni respondents (P <0.05). The variables of Islamic cohesion and national identity also had a statistically significant difference between the respondents of ethnic groups (P <0.05) while there was no statistically significant difference in the perception of sporting success between the respondents of different ethnic groups and religious groups (P <0.05).  The findings of the study emphasized the positive functions of sports success in the convergence of more religious and ethnic groups in the country.